Strategy for Instilling Trustworthy Character Using the Tumpe Method in Elementary School Students - Lamadang, Karmila; Mamat Supriatna; Sapriya; Nana Supriatna; Falimu (Elementary Teacher Education Program, Majalengka University, 2024)
The tumpe-based character education method is a strategy that is expected to be effective in instilling values ​​and character education in elementary school students. This approach is implemented at SDN Negeri 1 Toili, Banggai Regency with a focus on cultivating the character of Trustworthiness (Integrity). The Tumpe method is a participatory and experiential learning approach that involves students in the entire process. The aim of this research is to find out what the trustworthy character education strategy is using the Tumpe method at Toili 1 Elementary School, Banggai Regency. This research method is a qualitative descriptive method, namely a method that relies on observation, interviews and documentation. The research results show that the strategy of instilling character in school-age students is very important to become their educational capital in the future. The TUMPE method is an educational method that is easy to apply. Keywords: Strategy, Trustworthy Character, Method, Tumpe